ANALISIS KEAKTIFAN MAHASISWA DALAM PEMBELAJARAN DARING DENGAN E-LEARNING SEBAGAI DAMPAK DARI PANDEMI COVID-19 TAHUN 2020 - Reni Nugraheni; Hery Sawiji; Tri Murwaningsih (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2022)
This study aimed to find out: the activeness of students during the online learning process with E-Learning, the obstacles that arose in the implementation of online learning with E-Learning, and the efforts made to face the existing obstacles. This study used a qualitative research method with a case study approach. The data of this study obtained from informants, documents and archives. The sampling techniques used were purposive sampling and snowball sampling. The data collection techniques used were interviews, observation, documents, and archive analysis. The data validation was done through source triangulation and method triangulation. The data analysis technique used interactive model data analysis. The results showed that: (1) The activeness of students in implementing online learning with E-Learning during the 2020 COVID-19 pandemic was lack. (2) The obstacles in the implementation of online learning were: (a) low concentration of learning, (b) interactions that tend to be one-way, (c) less varied learning methods, (d) the internet network was less stable, (e) the difficulty of lecturers in controlling the class. The efforts to overcome obstacles were as follows: (a) provided ice-breaking, (b) used more varied learning methods, (c) provided stimulus by lecturers, (d) used different applications, (e) performed periodic control on students.